2012
DOI: 10.1071/cp12215
|View full text |Cite
|
Sign up to set email alerts
|

Fodder yield and quality in forage sorghum: scope for improvement through diverse male sterile cytoplasms

Abstract: Cytoplasmic male sterility (CMS) has proved to be an effective and efficient genetic tool in sorghum (Sorghum bicolor (L.) Moench) hybrid breeding programs. The A1 (milo cytoplasm) CMS type has been widely exploited to produce both commercial grain and forage sorghum hybrids. To explore the possibility of using alternative CMS (non-milo cytoplasm) sources, we studied the effect of cytoplasm on forage yield and quality in sorghum. Nine female (CMS) lines (representing three each in A1, A2, and A3 cytoplasms) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
5
0
2
Order By: Relevance
“…The result indicated that there is good scope for insect resistant improvement in sorghum through hybrid breeding. Similar results were reported by Agrawal and Abraham, 1984 [1] ; Tahir, 2005 [10] ; Aruna et al, 2013 [2] and reported that hybrid breeding can contribute to greater extent in breeding of resistant genotypes of forage sorghum.…”
Section: Resultssupporting
confidence: 88%
“…The result indicated that there is good scope for insect resistant improvement in sorghum through hybrid breeding. Similar results were reported by Agrawal and Abraham, 1984 [1] ; Tahir, 2005 [10] ; Aruna et al, 2013 [2] and reported that hybrid breeding can contribute to greater extent in breeding of resistant genotypes of forage sorghum.…”
Section: Resultssupporting
confidence: 88%
“…Genotype × environment interaction is commonly observed as the differential ranking of genotypes across environments (Mohammadi & Amri 2013) and GEI for forage yield and quality in forage sorghum has been reported earlier (Aruna et al . 2012). The GGE biplot is a tool to visualize the patterns of GEI in a graphical manner (Yan 2001; Yan & Tinker 2006), and also helps in identifying relationships among traits and detecting the best genotypes for different traits.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the cytoplasm can have a significant impact on the manifestation of these traits. There is a lot of data in the literature confirming the effect of the cytoplasm on agronomically valuable traits in wheat (Atienza et al, 2007), rice (Tao et al, 2011), cotton (Tuteja, Banga, 2011), pearl millet (Amiribehzadi et al, 2012), winter rye (Urban, Gordey, 2013), sorghum (Aruna et al, 2013), sunflower (Jan et al, 2014), maize (Kabanova et al, 2015), and mustard (Chakrabarty et al, 2015). Assuming that the manifestation of heterosis in F 1 hybrids is determined, in considerable extent, by the combining ability (CA) of maternal lines, investigation of the effect of cytoplasm on CA is of significant interest.…”
Section: Introductionmentioning
confidence: 99%